Oral hygiene practices and its relationship with periodontal status among police personnel of Bhopal city, Central India: An epidemiological study - Aishwarya Singh; Ajay Bhambal; Sudhanshu Saxena; Vidhatri Tiwari; Utkarsh Tiwari; Ratika Shrivastava (Wolters Kluwer Medknow Publications, 2015)
Background: To assess the oral hygiene practices, oral health awareness, and oral health status of police personnel in Bhopal city and to suggest measures to improve the present oral health status. Materials and Methods: The cross-sectional study was conducted on 781 subjects, mean aged 40.5 years, who were selected by simple random sampling. Type-III examination of the subjects was conducted and along with questionnaire, community periodontal index (CPI), loss of attachment index and decayed, missing, filled teeth (DMFT) data was recorded on modified W.H.O format 1997. A value of P ≤ 0.05 was considered statistically significant. Results: Awareness related to oral health diseases, its cause, and prevention was low among police personnel. DMFT was significantly lower among this group. CPI score 2 was highest among the majority of subjects. Subjects brushing twice daily had significantly healthy periodontium than those brushing once daily. Conclusion: Most of the police personnel lack oral health awareness and suffer from periodontal diseases. Awareness should be created to maintain good oral hygiene, regular dental checkup and refrain from smoking among police personnel.